Patent Foramen Ovale and Migraine: A Cross-Sectional Study from the Northern Manhattan Study (NOMAS) - Rundek, Tatjana (2008)
BACKGROUND: A causal relationship between patent foramen ovale (PFO) and migraine has been hypothesized, and improvement of migraine frequency and severity after percutaneous PFO closure has been reported. Population-based data on the relationship between PFO and migraine are however sparse. The objective of this study was to examine the association between PFO and migraine among stroke-free individuals in an urban, population-based multiethnic cohort. METHODS AND RESULTS: As a part of the ongoing Northern Manhattan study (NOMAS), 1,101 stroke-free subjects were assessed for self-reported history of migraine. The presence of PFO was assessed by transthoracic echocardiography. The mean age of the group was 69±10 years; 58% were women; 48% Caribbean Hispanic, 24% white, 26% black, and 2% other race-ethnicity. The prevalence of self-reported migraine was 16% (13% migraine with aura). The prevalence of PFO was 15%. Migraine was significantly more frequent among younger subjects, women, and Hispanics. The prevalence of PFO was not significantly different between subjects who had migraine (26/178, or 14.6%) and those who did not (138/923, or 15.0%; p=0.9). In an adjusted multivariate logistic regression model, the presence of PFO was not associated with increased prevalence of migraine (odds ratio, OR 1.01; 95% Confidence Interval, CI 0.63–1.61). Increasing age was associated with lower prevalence of migraine in both subjects with a PFO (OR 0.94, 95% CI 0.90–0.99 per year) and without PFO (OR 0.97, 95% CI 0.95–0.99 per year). The observed lack of association between PFO and migraine (with or without aura) was not modified by diabetes, hypertension, cigarette smoking, and dyslipidemia. CONCLUSION: In this multiethnic elderly population-based cohort, PFO detected with TTE and agitated saline was not associated with self-reported migraine. The causal relationship between PFO and migraine remains uncertain, and the role of PFO closure among unselected patients with migraine remains questionable.